2002
DOI: 10.1099/0022-1317-83-6-1477
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequences of segments 1, 3 and 4 of the genome of Bombyx mori cypovirus 1 encoding putative capsid proteins VP1, VP3 and VP4, respectively

Abstract: The complete nucleotide sequences of genomic segments S1, S3 and S4 from Bombyx mori cypovirus 1 (BmCPV-1) have been determined. The segments consisted of 4190, 3846 and 3262 nucleotides encoding putative proteins of 1333, 1239 and 1058 amino acids with molecular masses of approximately 148, 140 and 120 kDa (p148, p140 and p120, respectively). All segments possess a single open reading frame. Homology searches showed that all three proteins have homologies to proteins of Rice ragged stunt virus, a member of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 16 publications
1
27
0
1
Order By: Relevance
“…Genomic dsRNA of UsCPV was extracted from purified polyhedra by using a QIAampViral minikit from Qiagen (13,24). The RNA was precipitated, washed with 75% ethanol, dried under a vacuum, and resuspended in RNase-free water.…”
Section: Methodsmentioning
confidence: 99%
“…Genomic dsRNA of UsCPV was extracted from purified polyhedra by using a QIAampViral minikit from Qiagen (13,24). The RNA was precipitated, washed with 75% ethanol, dried under a vacuum, and resuspended in RNase-free water.…”
Section: Methodsmentioning
confidence: 99%
“…The molecular weight of the P3 protein of RRSV (131K) is similar to that of the major capsid shell VP1 protein of CPV (148K) and the 1 protein of Orthoreovirus (142K). The P3 protein of RRSV has partial homologies to the major capsid shell VP1 protein of CPV (12,13), which has conserved holding and protein organization among capsid shell proteins of the reoviruses (37,42). Indeed, the secondarystructure prediction showed that the P3 protein of RRSV contains many ␣-helical elements in addition to the ␤-strand elements, which suggests that the P3 protein of RRSV has ␣ ϩ ␤ holds, a structure similar to those of other members of Reoviridae (3).…”
Section: Resultsmentioning
confidence: 99%
“…The turrets of RRSV are larger than those of Orthoreovirus (28) and CPV (approximately 150 Å in diameter and 100 Å in height in both cases) (42). RRSV contains at least six structural proteins, namely P1, P2, P3, P4A, P8B, and P9, with molecular weights of 138,000 (138K), 133K, 131K, 141K, 42K, and 39K, respectively (13,15,(32)(33)(34), that are encoded by 10 segments of the dsRNA genome (26). The capsid of RRSV, encapsidating RdRp (P4A protein) (33) and 10 segments of dsRNA, appears to consist of at least four kinds of protein: P2, a capping enzyme (31); P3, a capsid shell protein (13); P8, a major capsid protein that is cleaved to yield P8A and P8B (32); and P9, a spike protein involved in transmission via the insect vector (6a, 34, 41).…”
mentioning
confidence: 99%
“…However, information regarding the genomic makeup of CPVs is rather limited. The complete nucleotide sequences for only three CPV types (1, 14, and 15) have been reported and deposited into GenBank [9,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%